Documentary evidence on weather conditions and a possible crisis in 1315-1317: case study from the Carpathian Basin - Vadas, András (Journal of Environmental Geography, 2009)
In the last decades, climate variabilites of the fourteenth century gained great interest and became a subject of numerous research papers. Due to the relative lack of sources referring to the climate of the Carpathian Basin, merely based on written evidences continuous climate reconstruction of the period is not possible. Nevertheless, there are cases when, due to available contemporary evidence, still some conclusions can be drawn. In this paper an investigation is carried out on one specific environmental crisis characterized by several flood events of European rivers caused by repeated abundant rainfalls; moreover, summer and winter temperatures were lower than the average of the preceding century. As a result of unfavorable environmental and economic conditions, a great number of Western and Central European sources reported on famines caused by the destruction of cereals. Mainly based on Austrian and Czech narratives as well as Hungarian charters, in the present paper an attempt was made to collect all the available sources on prevailing weather conditions and their possible effects in the Hungarian Kingdom mainly referring to the period of 1315-1317.